2021
DOI: 10.1177/23259671211015207
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Open Versus Arthroscopic Broström Surgery for Chronic Lateral Ankle Instability: A Systematic Review and Meta-analysis of Comparative Studies

Abstract: Background: Nearly 20% of acute ankle sprains progress to chronic lateral ankle instability that requires surgical intervention. In recent years, there has been a growing interest in arthroscopic Broström techniques as an alternative to open surgery. Purpose: To review the most up-to-date evidence comparing the outcomes of open and arthroscopic Broström procedures for chronic lateral ankle instability. Study Design: Systematic review; Level of evidence, 3. Methods: This review was performed following the PRISM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 32 publications
2
21
0
Order By: Relevance
“…With recent advances in technology, surgeons are showing more interest in arthroscopic procedures, and their clinical outcomes are comparable to those of traditional open Broström procedures. 2 However, the recurrence of postoperative instability remains a major concern. 35 Although anatomic factors have been reported as risk factors for recurrent instability after lateral ankle ligament repair, 44 there is a lack of data in the literature delineating the risk factors, including activity level, remnant quality, and repair techniques.…”
Section: Introductionmentioning
confidence: 99%
“…With recent advances in technology, surgeons are showing more interest in arthroscopic procedures, and their clinical outcomes are comparable to those of traditional open Broström procedures. 2 However, the recurrence of postoperative instability remains a major concern. 35 Although anatomic factors have been reported as risk factors for recurrent instability after lateral ankle ligament repair, 44 there is a lack of data in the literature delineating the risk factors, including activity level, remnant quality, and repair techniques.…”
Section: Introductionmentioning
confidence: 99%
“…These results are approximately similar to the results of a systematic review performed by Guelfi et al, 15 which included a total of 505 patients and revealed mean scores of 90.1 for the AOFAS in the open Brostrom procedure group. The VAS score indicated good results, and the overall average scores of the 2 groups and treatment groups were lower than those of a systematic review performed by Attia et al 2 The total ROM scores in the control group declined significantly compared with the PRP group after 3 months ( P = .030) (Tables 2 and 3). However, the difference was not clinically relevant (4.6 degrees).…”
Section: Discussionmentioning
confidence: 62%
“…Moreover, biomechanical studies found no significant difference in fixation strength between open procedure and ABG [12,13]. ABG had become the standard treatment for CAI, with a small incision, less invasiveness, shorter hospital stay, improved functional recovery, and concomitant intraarticular lesion treatment under arthroscopy [14][15][16].…”
Section: Introductionmentioning
confidence: 99%